The Car Interior of the Future: Where 3D Data Makes the Difference - Pele Anne Francoise (Ee Times Europe, 2022)
Transformational Transformer Networks, Cloudification Demands Timing Design Shift, AVs: How Is Europe Doing?, Democratizing Space and Protecting the Planet.